IMPLEMENTATION OF AN ENTREPRENEURSHIP LEARNING MODEL IN THE CREATIVE PRODUCT AND ENTREPRENEURSHIP COURSE FOR VOCATIONAL HIGH SCHOOLS - Syamsudin, Rudi Nur; Ikhwanuddin, Ikhwanuddin; Prihadi, Wisnu Rachmad; Malik, Abdul (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The learning model is one of the main factors that need to be considered in the learning process. This study aims to reveal the effect of applying the “EkRenFaTiHa” entrepreneurship learning model in vocational high schools. The research design is quasi-experimental. Determination of the sample using the purposive sampling technique. Data collection techniques using observation, documentation, and tests the prerequisite tests carried out are validity tests, reliability tests, normality tests, and hypothesis tests. The research location was in class XI at one of the state vocational schools in the Province of DIY. It was agreed with the school that it was not permissible to mention the name of the school, so the research location was named X’s vocational high schools. The results of the hypothesis testing showed that the cognitive value in the experimental class was significant, which was 0.001, where the value was < 0.05. This means that the “EkRenFaTiHa” entrepreneurship learning model can have a significant influence on student learning outcomes in the subject of creative products and entrepreneurship. While the value of product results in the experimental class is still higher than in the control class. The experimental class got an average product value of 75.455, while the control class average product value was 74.773.